HEALTH EDUCATION UNTUK MENINGKATKAN MANAJEMEN HIPERTENSI PADA PASIEN HIPERTENSI - Rina, Rina; Jurisa, Enny; Budi, Setia; Dian Ardianti, Riski; Steffi Harkensia, Linur; Novebrina, Hilda; Nabila, Putri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Life expectancy (LE) is one indicator of development success, especially in the health sector. A healthy nation is characterized by a longer life expectancy. With increasing age, physiological changes will occur, especially in the elderly, and various health problems will arise (Berlian et al., 2022). The 2023 Indonesian Health Survey (SKI) found the prevalence of hypertension in West Sumatra to be 24.1%. The highest prevalence of hypertension in West Sumatra was in Padang City, at 35.6%. Meanwhile, the lowest prevalence of hypertension was in West Pasaman Regency, at 19.8%. The 2022 Padang City health profile data shows an estimated number of hypertension sufferers aged 15 years and above, amounting to 165,555 people. The qualitative descriptive method used was observation, interviews, and documentation, with face-to-face meetings involving 25 participants. The program included blood pressure checks, outreach, material presentations, discussions, questions and answers, and pre- and post-test evaluations. Prior to the counseling session, blood pressure was checked and a pre-test questionnaire provided by the counselor was completed. Following the counseling session, participants' understanding significantly improved. This was evident in their post-test scores. Seventy-five percent of participants answered the post-test questions correctly.